Study sorption and desorption of Cd+2, Pb+2 ions by selected chelating resin to removal them from industrial and environmental wastes - Ahmed D. Saleh; Muthana M. Sirhan; Ali S. Ismail (Energy Reports, 2020)
A paper reports study of sorption and desorption behavior of Cd+2, Pb+2 ions on selected chelating resin consists of (P-DETATA). It had converted to sodium form by treated with basic solution (0.5 M, NaOH). Sorption studies of Cd+2 and Pb+2 ions were carried out by using batch-column processing system, and total capacity (mmoles of Mn+/g dry resin) was designed as a function of pH values, time periods and constant temperature. As well, desorption of Cd+2 and Pb+2 ions were achieved using diverse concentrations of diluted HCl at flow rate of 1 ml/min using column method. The results obtained indicate that the (P-DETATA) resin has higher affinity towards the metal ions under the study. This may give opportunity to use it for removing of Cd+2 and Pb+2 ions from industrial and environmental wastes.
Keywords: 330; (P-DETATA); Bech-column; Chelating resin; Industrial and environmental; Sorption and desorption